2021
DOI: 10.1021/acs.inorgchem.1c03004
|View full text |Cite
|
Sign up to set email alerts
|

Cation- and Anion-Mediated Supramolecular Assembly of Bismuth and Antimony Tris(3-pyridyl) Complexes

Abstract: The use of antimony and bismuth in supramolecular chemistry has been largely overlooked in comparison to the lighter elements of Group 15, and the coordination chemistry of the tripodal ligands [Sb(3-py) 3 ] and [Bi(3-py) 3 ] (L) containing the heaviest p-block element bridgehead atoms has been unexplored. We show that these ligands form a common hybrid metal–organic framework (MOF) structure with Cu(I) and Ag(I) (M) salts of weakly coordinating anions (PF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…16,17 The coordination of the tris (3-pyridyl) and tris(4pyridyl) ligands to Cu and Ag salts gives extended structures involving a combination of N-donor and bridgehead-donor bonding (intermolecular coordination, Figure 1b). 18,19 Despite increasing interest in this area, the elaboration of this type of ligand using extended N-donor polyaromatic donor groups has been largely ignored as a means of modifying the coordination character. The first example of this type containing a heavier element bridgehead was MeSi(3-qy) 3 (qy = quinolyl), 20−22 effects and the geometric constraints imposed by the orientation of the donor quinolyl N atoms (Figure 1c).…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…16,17 The coordination of the tris (3-pyridyl) and tris(4pyridyl) ligands to Cu and Ag salts gives extended structures involving a combination of N-donor and bridgehead-donor bonding (intermolecular coordination, Figure 1b). 18,19 Despite increasing interest in this area, the elaboration of this type of ligand using extended N-donor polyaromatic donor groups has been largely ignored as a means of modifying the coordination character. The first example of this type containing a heavier element bridgehead was MeSi(3-qy) 3 (qy = quinolyl), 20−22 effects and the geometric constraints imposed by the orientation of the donor quinolyl N atoms (Figure 1c).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Tripodal, facially coordinating tris (pyridyl) ligands have far-reaching applications in coordination, organometallic catalysis, and supramolecular chemistry. , The selection of the bridgehead atom and the position of the N-donor atoms in the pyridyl rings have a fundamental impact on the behavior and coordination properties of this family of ligands. , Classically, studies have focused on tris (2-pyridyl) ligands containing nonmetallic bridgehead atoms, E­(2-py) 3 (e.g., E = CR, COR, CH, N, P, PO; 2-py = 2-pyridyl) . However, incorporating heavier and more metallic main-group bridgehead atoms has been shown to provide an important tool for tuning the ligand character, enabling systematic modification of the bite angle, donor/acceptor properties, and reactivity. , Recent studies have explored the coordination chemistry of tris (2-pyridyl) ligands based on Sb and Bi, which coordinate metals (e.g., Cu + , Ag + , Li + ) through the three pyridyl arms in an N , N , N -chelate coordination mode, which is typical of the tris (2-pyridyl) family (intramolecular coordination, Figure a). , In addition, changing the position of the pyridyl N-donor atom from the 2- to the 3-position with respect to the bridgehead atom/group significantly changes the coordination behavior of the ligands, permitting the coordination of multiple metal centers. , The coordination of the tris (3-pyridyl) and tris (4-pyridyl) ligands to Cu and Ag salts gives extended structures involving a combination of N-donor and bridgehead-donor bonding (intermolecular coordination, Figure b). , …”
Section: Introductionmentioning
confidence: 99%
“…We have very recently developed synthetic approaches to metallic or semi-metallic tris-pyridyl ligands, [42][43][44][45][46][47] including the heavier Group 15 ligands E(3-py) 3 [E = Sb (1), Bi (2)] (Fig. 2a), 48 and shown that the latter can be employed in the construction of a series of hybrid MOF arrangements with Cu + and Ag + (=M + ) salts, in which the ligands adopt a tetradentate N,N,N,E-bonding mode. 48 As shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…2a ), 48 and shown that the latter can be employed in the construction of a series of hybrid MOF arrangements with Cu + and Ag + (=M + ) salts, in which the ligands adopt a tetradentate N,N,N,E-bonding mode. 48 As shown in Fig. 2b , these MOFs consist of E 4 M 4 cubane units in which the anions are encapsulated.…”
Section: Introductionmentioning
confidence: 99%
“…Organostibines have gained great attention in the past decades and are widely used in Lewis acids, ligands, catalysts, and gas fixation . We are interested in C–C and C–Z (Z = O, S, Se N etc.)…”
mentioning
confidence: 99%